Sources and significance of variation in basal, summit and maximal metabolic rates in birds - Mckechnie, Andrew E.; Swanson, David L. (Current Zoology, 2010)
The rates at which birds use energy may have profound effects on fitness, thereby influencing physiology, behavior, ecology and evolution. Comparisons of standardized metabolic rates （e.g., lower and upper limits of metabolic power output） present a method for elucidating the effects of ecological and evolutionary factors on the interface between physiology and life history in birds. In this paper we review variation in avian metabolic rates [basal metabolic rate （BMR; minimum normothermic metabolic rate）, summit metabolic rate （Msum; maximal thermoregulatory metabolic rate）, and maximal metabolic rate （MMR; maximal exercise metabolic rate）], the factors associated with this variation, the evidence for functional links between these metabolic traits, and the ecological and evolutionary significance of avian metabolic diversity. Both lower and upper limits to metabolic power production are phenotypically flexible traits, and vary in association with numerous ecological and evolutionary factors. For both inter- and intraspecific comparisons, lower and upper limits to metabolic power production are generally upregulated in response to energetically demanding conditions and downregulated when energetic demands are relaxed, or under conditions of energetic scarcity. Positive correlations have been documented between BMR, Msum and MMR in some, but not all studies on birds, providing partial support for the idea of a functional link between lower and upper limits to metabolic power production, but more intraspecific studies are needed to determine the robustness of this conclusion. Correlations between BMR and field metabolic rate （or daily energy expenditure） in birds are variable, suggesting that the linkage between these traits is subject to behavioral adjustment, and studies of the relationship between field and maximal metabolic rates are lacking. Our understanding of avian metabolic diversity would benefit from future studies of： （1） the functional and mechanistic links between lower and upper limits of metabolic power output; （2） the environmental and ecological cues driving phenotypically flexible metabolic responses, and how responses to such cues might impact population responses to climate change; （3） the shapes of metabolic reaction norms and their association with environmental variability; and （4） the relationship of metabolic variation to fitness, including studies of repeatability and heritability of minimum and maximum metabolic power output [Current Zoology 56 （6）： 741-758, 2010].